Scientific Research Trends of Flooding Stress in Plant Science and Agriculture Subject Areas (1962-2021) - Nurrahma, Arinal Haq Izzawati; Putri, Hana Haruna; Syahadat, Ray March (ASEAN Journal of Science and Engineering, 2023)
Data collection was gathered from PubMed, Google Scholar, Semantic Scholar, and Crossref in Harzing”s Publish or Perish software. The keyword used in this study was "Flooding Stress" with the publication year of the 1962-2021 articles. Results showed that PubMed retrieves more relevant manuscripts from journal sources than other databases. The search method by whole years was the most effective and efficient if the total manuscripts are less than 1000. Flooding stress-related manuscripts were published continuously from 1994 to 2021 with Annals of Botany as the most productive journal. A combination of “Flooding Stress” with related keywords, e.g., submergence stress, anaerobic stress, and oxidative stress, improves the relevancy of the manuscript results. VOSviewer keyword analysis found that there were 5 clusters discussing oxidative stress, tolerant mechanism, physiological mechanism, flood occurrence, and molecular mechanism. Based on the density visualizations, the anaerobic metabolism, mRNA expression level, SOD, fv/fm, leaf gas exchange, ABA biosynthesis, and halophyte lead to potential topics of flooding stress research to be studied in the future.